Using empathy approach to design type-2 diabetic user persona - Imhemed, Serag M.; Kamaruddin, Azrina; Atan, Rodziah (2017)
Empathy approach can be utilized as a tool to uncover sensory information. It also uncovers the experience of target-audience and builds a better understanding of their behaviors and concerns, incorporating them as user-profiles and personas. Modern technology draws a lot of success from how relatable it is to the average person, when designing an interactive technology, the human element is of the highest significance. To develop usable, high efficient and user-friendly application, we must understand, capture and analyze the essence of target audience issues and concerns. This helps the development team to cognitively imagine and communicate how the end-user will interact with the proposed design in a meaningful way. Type-2 diabetes is unquestionably a life-altering incident; to be able to fully understand it, one must focus less on the technical aspects of the issue and more on the human aspects. This research paper adopts an action ethnography approach to create a degree of empathy for diabetic users; bring attention to the significance of health related characteristics for type-2 diabetes personas and demonstrate the process and usefulness of these tools in user requirement gathering, design and implementation planning.